2016
DOI: 10.4103/0253-7184.176215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of syndromic management measured as symptomatic improvement in females with vaginal discharge syndrome

Abstract: Background:In spite of a few shortcomings such as over diagnosis and over treatment, syndromic management is a recommended practice in India for sexually transmitted infections (STIs). This study tries to find out the efficacy of syndromic management measured as symptomatic improvement in females with vaginal discharge syndrome.Objective:The objective of the study is to find out the effectiveness of syndromic management in terms of symptomatic improvement among females with vaginal discharge syndrome.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…In this study syndromic management effective in 65.39% women of reproductive age group. Chauhan et al and Singh et al showed syndromic management effective in relieving symptoms in most of the cases which is comparable to this study 1,17.…”
supporting
confidence: 89%
“…In this study syndromic management effective in 65.39% women of reproductive age group. Chauhan et al and Singh et al showed syndromic management effective in relieving symptoms in most of the cases which is comparable to this study 1,17.…”
supporting
confidence: 89%
“…As such, asymptomatic individuals continue to spread infection and become susceptible to long term STI complications. Syndromic management often promotes over-diagnosing and over-treating because treatment is issued often targeting the most common STI causative pathogens instead of a speci c pathogen (13,14). As such Murewanhena et al (14) suggest a shift from syndromic management of STIs to a more pathogen speci c diagnosis and treatment of STIs.…”
Section: Introductionmentioning
confidence: 99%
“…As such, asymptomatic individuals continue to spread infection and become susceptible to long term STI complications. Syndromic management often promotes over-diagnosing and over-treating because treatment is issued often targeting the most common STI causative pathogens instead of a specific pathogen 13 , 14 . As such Murewanhena et al 14 suggest a shift from syndromic management of STIs to a more pathogen specific diagnosis and treatment of STIs.…”
Section: Introductionmentioning
confidence: 99%